Visual cortex anodal transcranial direct current stimulation does not alter reading performance for Chinese presented character-by-character to normal peripheral vision in older adults - Lyu, Anqi; Silva, Andrew E.; Thompson, Benjamin; Abel, Larry; Cheong, Allen M. Y. (Frontiers in Neuroscience, 2024)
Visual cortex anodal transcranial direct current stimulation (a-tDCS) has been shown to reduce crowding in normal peripheral vision and may improve the reading of English words in patients with macular degeneration. Given the different visual requirements of reading English words and Chinese characters, the effect of a-tDCS on peripheral reading performance in English might differ from Chinese. This study recruited twenty participants (59 to 73 years of age) with normal vision and tested the hypothesis that a-tDCS would improve the reading of Chinese characters presented at 10 o eccentricity compared with sham stimulation. Chinese sentences of different print sizes and exposure durations were presented one character at a time, 10 o below or to the left of fixation. The individual critical print size (CPS) -the smallest print size eliciting the maximum reading speed (MRS) -was determined. Reading accuracies for characters presented 0.2 logMAR smaller than the individually fitted CPS were measured at four time points: before, during, 5 minutes after, and 30 minutes after receiving active or sham visual cortex a-tDCS. Participants completed both the active and sham sessions in a random order following a double-blind, within-subject design. No effect of active a-tDCS on reading accuracy was observed, implying that a single session of a-tDCS did not improve Chinese character reading in normal peripheral vision. This may suggest that a-tDCS does not significantly reduce the crowding elicited within a single Chinese character. However, the effect of a-tDCS on between-character crowding is yet to be determined.